2008
DOI: 10.1017/s0022029908003336
|View full text |Cite
|
Sign up to set email alerts
|

Fat content and fatty acids profile of colostrum and milk of primitive Konik horses (Equus caballus gmeliniAnt.) during six months of lactation

Abstract: The effect of the stage of lactation, the number of foals and age of the mare on changes in the fat content and fatty acid composition of colostrum and milk of primitive Konik horses was investigated. Colostrum and milk samples from 12 lactating mares were collected at the beginning of lactation, on the days 1 and 2 after foaling and then, starting from the first month of lactation, at 4-week intervals up to the sixth month of lactation. Significant differences were observed in fat content as well as the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
52
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 12 publications
10
52
0
1
Order By: Relevance
“…As a consequence, the FO diet decreased values of the concentration ratios of SFAs to the sum of PUFAs ( PUFAs) and the sum of LPUFAs ( LPUFAs) in the brain compared with the RO diet. The present results documented that the diet enriched in FO reduced the brain concentration of C14:0, which is considered to be 4 times more atherogenic than the other SFAs (like C12:0 or C16:0) (Pikul et al, 2008). The FO diet can prevent atherosclerosis (i.e.…”
Section: The First Experimentsmentioning
confidence: 64%
See 3 more Smart Citations
“…As a consequence, the FO diet decreased values of the concentration ratios of SFAs to the sum of PUFAs ( PUFAs) and the sum of LPUFAs ( LPUFAs) in the brain compared with the RO diet. The present results documented that the diet enriched in FO reduced the brain concentration of C14:0, which is considered to be 4 times more atherogenic than the other SFAs (like C12:0 or C16:0) (Pikul et al, 2008). The FO diet can prevent atherosclerosis (i.e.…”
Section: The First Experimentsmentioning
confidence: 64%
“…As expected, our study indicated that the FO diet also decreased index A SFA and index T SFA as well as the concentration ratios of A SFA and T SFA to n-3PUFA in the brain compared with the RO diet ( Table 3). The A SFA / n-3PUFA and T SFA / n-3PUFA ratios are the relationship between A SFA and T SFA as well as n-3PUFAs; n-3PUFAs play of critical roles in preventing atherosclerosis and thrombosis (Pikul et al, 2008;Garaffo et al, 2011). Thus, current study and other investigations (Pikul et al, 2008;Garaffo et al, 2011) indicated that, in contrast to the RO diet, the FO diet (rich in n-3LPUFA) reduced the risk of the pathological changes in cerebral vessels (i.e.…”
Section: The First Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The beneficial effect of the bioactive components contained in milk and its products on consumer health is well documented (Myers, 2007). The level of bioactive components in raw milk, especially fatty acids, is determined, among others, by the animal species, diet and stage of lactation Pikul et al, 2008;Markiewicz-Kęszycka et al, 2014). Sheep milk has a greater nutritional value than cow, or even goat milk.…”
Section: Introductionmentioning
confidence: 99%